Species composition of amphibians (Amphibia) and reptiles (Reptilia) from Hagiang province - Truong, Nguyen Quang; Ngat, Le Nguyen; Bain, Raoul (Academia Journal of Biology, 2014)
During the period from 2000 to 2005, five surveys on the herpetofauna were conducted in the Muongcha mountain (Yenminh district), the Tayconlinh mountain (Vixuyen district) and the Dadin mountain (Xinman district), of the Hagiang province. A total of 67 herptile species were recorded in these areas, including 35 amphibian species belonging to 7 families, 2 orders and 32 reptilian species belonging to 10 families, 2 orders. Among them, one new species to science was described Rana iriodes Bain and Nguyen, 2004; two species of salamanders Tylototriton asperrimus (Unterstein, 1930) and Paramesotriton cf. deloustali (Bourret, 1934) were found in the Tayconlinh mountain as provincial first records and the distribution of these threatened species were expanded in the North of Vietnam. 6 species were listed in the Governmental Decree No 32/2006/ND-CP; 9 species were listed in the Red Data Book of Vietnam (2000) and 8 species were listed in the IUCN Red List (2004).